Study of Driver Gap Acceptance Behavior at Merging Area in Baghdad City - I. AL-Kubaisi, Mehdi (Iraqi Journal of Civil Engineering, 2007)
AbstractThis paper describes a traffic behavior at merging (on-ramp) area in Baghdad city. The objective is to predict the acceptable and critical gap necessary for completing merging process in an on-ramp area for vehicles to enter the highway based on observed traffic data.Data were collected from two selected sites which had certain characteristics both operational and geometrical to fit the criteria needed for gap acceptance study which were presented hereinafter. These two sites were on-ramp sections at Mohamed Al-Qasim highway and the Army-Canal highway.Video-recording equipments were used to collect data. The observed data were analyzed, grouped, and processed using computer programs developed by the researcher for this purpose. Standard statistical analysis techniques were used to examine and analyze the observed data.Gap acceptance results are used to determine the critical gap. Critical gaps are playing main role to evaluate level of service and capacity at Highway merging sections. This study measures gaps in the major stream regarding to driver behavior for traffic stream in the merging area. It has been found that different types of drivers will accept different gaps, more aggressive drivers will accept smaller gaps and conservative drivers accept larger gaps.Keywords / Traffic behavior, Gap acceptance, Critical gap, Merging area, Highway capacity.